Anaerobic co-digestion of food waste for biohydrogen production - Jamil, Z.; Yunus, N.A.M.; Suffian, M.; Ibrahim, S. (2013)
The objective of this study was to find the optimum conditions for anaerobic co-digestion of food waste and sewage sludge and hydrogen (H 2) production. The selected parameters for optimization of H 2 production (e.g. temperature, initial pH, inoculum size) were analysed using Response Surface Methodology with Full Factorial Design. Two types of substrates were tested; food waste as a sole substrate and food waste mixed with palm oil mill effluent (POME) at volume ratio1:1. The optimized conditions for food waste as a sole substrate were pH 4.5, temperature of 35°C and inoculum size of 20 (v/v), with maximum predicted cumulative hydrogen production (MPCHP) of 0.22 ml H2/ml substrate. On the other hand, for food waste mixed with POME, pH 4.5, temperature of 35°C and inoculum size of 20 were the optimum conditions with MPCHP of 0.26 ml H 2/ml substrate. Subsequently, verification experiments at optimal parameter values yielded cumulative H2 of 0.28 ml H2 /ml substrate for food waste only, and 0.33 ml H2/ml substrate for food waste mixed with POME. © 2013 IEEE.